High prevalence of arrhythmias in elderly male athletes with a lifelong history of regular strenuous exercise - Jensen-Urstad, K (1998)
Objective—To characterise cardiac arrhythmias and cardiac autonomic function in 11 elderly men (mean (SD) age 73.2 (2.8) years) with a lifelong history of regular very strenuous exercise. A control group of 12 healthy sedentary or moderately physically active men (74.5 (2.7) years) was also studied. Design—48 hour ambulatory electrocardiograms were recorded. Cardiac autonomic function was estimated from power spectral analysis of heart rate variability. Maximal oxygen uptake during treadmill exercise testing was 2.91 (0.52) l (41 (7) ml/kg). Results—Nine of 11 athletes had complex ventricular arrhythmias compared with five of 12 controls. Seven athletes but none of the controls had episodes of heart rate below 40 beats/min and two athletes had RR intervals longer than two seconds. Heart rate variability in the athletes was higher than in the controls.  Conclusions—Elderly athletes with a lifelong training history seem to have more complex arrhythmias and profound bradyarrhythmias than do healthy elderly controls, which may increase the risk of sudden cardiac death. In contrast, the age related decrease in heart rate variability seems to be retarded, which has a positive prognostic value and may decrease the risk of life threatening ventricular arrhythmias.   Keywords: arrhythmias;  heart rate variability;  athletes;  exercise;  elderly men